Respuesta :

Answer:

(3,5)

Step-by-step explanation:

To solve the system using the substitution method start by isolating one of the variables in the first equation.

4x+7y-7y=47 -7y

4x/ 4= (-7y+ 47)/4

x= -1.75y+ 11.75

Next, substitute x= -1.75y+ 11.75 into equation 2 replacing x.

5( -1.75y+ 11.75)-4y=-5

-8.75y+58.75 -4y=-5

-8.75y+58.75- 58.75 -4y=-5- 58.75

-8.75y-4y=-63.75

(-12.75y)/-12.75y =(-63.75)/-12.75y

y= 5

Last, substitute y=5 into equation 1 and solve.

4x+7(5)=47

4x+35-35=47-35

4x=12

x=3